Using Multi-Grade Teaching in Strengthening Students' Character Post-FTF Learning - Wasehudin, Wasehudin; Wathoni, Kharisul; Hassan, Razali Bin; Anshori, Irfan; Faisal Akbar, Muhammad (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This research aims to learn multigrade teaching techniques to strengthen students' character values. Research methods include descriptive research through a qualitative approach. Researchers collect data through interviews, observation, and documentation. Qualitative data analysis is the collection, simplification, presentation of data, and conclusion. The results of this study describe that multi-grade teaching is closely related to strengthening the character values of post-face-to-face learning students. The process includes combining several grade levels with a maximum number of 25 students and then being given material by one teacher who emphasizes the learning process for students. The technique provides opportunities for students to improve the character values they have obtained. This technique encourages students to grow in learning effectively and efficiently and strengthens the character of students after the last 2 years, and students rarely meet with teachers. Some of the values obtained through multi-grade teaching: are independence, ethics, and cohesiveness.